anonymous
  • anonymous
HELP PLEASE? WILL MEDAL! (: Generate the first five terms of this sequence: f(1) = 1 and f(2) = 2, f(n) = f(n-1) + f (n-2) for n>2 A) 1, 2, 3, 4, 5 B) 1, 2, 3, 5, 7 C) 1, 2, 3, 5, 8 D) 1, 3, 5, 7, 9
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
f(3)=f(2)+f(1)=2+1=3 you can find other terms like this.
anonymous
  • anonymous
Okay so, f(1) = f(2) and f(n-1) + f(n-2)?
anonymous
  • anonymous
I don't even know if i'm making any sense rn, but i'm gonna try to understand haha!

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

Nnesha
  • Nnesha
n= term that you hve to find so to find 3rd term you should replace n with 3
Nnesha
  • Nnesha
\[\huge\rm f(\color{Red}{n}-1) = f(\color{ReD}{3}-1)\] solve the parentheses 3-1 =2 that's how he got f(2)
Nnesha
  • Nnesha
\[\huge\rm f(\color{Red}{3}) = f(\color{ReD}{3}-1)+f(\color{Red}{3}-2)\] solve the parentheses 3-1 =2 that's how he got f(2) 3-1 is one so f(3) = f(2)+f(1) now replace f(2) and f(1) with their values
Nnesha
  • Nnesha
given f(1)= 1 f(2) = 2 so substitute f(1) for 1 f(2) for 2
anonymous
  • anonymous
So where do those 1, and 2 go? I don't see f(2) or f(1) in the equation that you put above which is the f(3) = f(3-1) + f(3-2)
anonymous
  • anonymous
@Nnesha
Nnesha
  • Nnesha
yes replace f(1) and f(2) given is : f(1) = 1 f(2) =2 so plug them in \[\huge\rm f(\color{Red}{3}) = f(\color{ReD}{3}-1)+f(\color{Red}{3}-2)\] f(1) = 1 f(2) =2 so plug them in \[\huge\rm f(\color{Red}{3}) = \color{ReD}1+\color{Red}{2}\] 1+2 = 3 so f(3) = 3 now replace n with 4 to find 4th term

Looking for something else?

Not the answer you are looking for? Search for more explanations.